(untitled) (Communications in Computational Physics, 2025)
The gas separation phenomenon of the pressure-driven binary mixture (helium–argon) flows in a microchannel is investigated numerically over a wide range of Knudsen numbers using the discrete unified gas kinetic scheme. The effects of inlet/outlet pressure ratio and Knudsen number on gas separation are studied numerically. It is found that the separation is strengthened with the increase of pressure ratio, and exhibits different trends under different rarefied conditions. The degree of gas separation changes nonlinearly with the outlet Knudsen number and exhibits a maximum in the transitional regime. In particular, we find that the relative pressure deviation and the velocity ratio between light species helium and heavy species argon can be served as indicators for gas separation under different working conditions. Finally, the phenomenon of Knudsen minimum is observed for the light species and gas mixture in the transition regime, but it does not appear for the heavy species within the considered Knudsen number range (≤10).